An investigation into the presence of earnings management in U.S. large-cap companies. - Chew, Jia Yi. (2011)
This study is based on the observation that analysts’ consensus EPS forecast is exceeded by actual EPS but at the same time, analysts’ consensus RPS forecast exceeds actual RPS. Earnings management is conjectured to be one of the reasons for this phenomenon and this conjecture will be justified by a series of tests. S&P 500 companies that display the above mentioned trend in any quarter between the years 2007 to 2009 will be tested for abnormal operating margin and they will be flagged based on the extent of deviation from the proxy of their operating margin. Subsequently, they will be tested for abnormal current accruals by comparing with their industry peers. Several firms tested positive for these series of tests. This report then discusses whether it is possible to stretch operating margin to such an extent and reason whether earnings management could be a cause instead.